Pengaruh Promosi Kesehatan Keluarga Terhadap Peran Keluarga Dalam Pengelolaan Anggota Keluarga Dengan Diabetes Mellitus Di Puskesmas Kebakkrmat I - Yeni Nur Rahmayanti (Jurnal Infokes, 2020)
There are 90% diabetes mellitus sufferers in the world. Diabetes mellitus (DM) is a degenerative disease that has increased every year in countries. Diabetes Mellitus if not handled properly will lead to complications. Cooperation between patients and families is expected to prevent chronic complications of DM, by providing information through health promotion. In this study using "pre post test non control group design" where a group before a certain treatment (x) is given a pretest, then given treatment and after the treatment is carried out a post test or a measurement to determine the consequences of the treatment. The independent variable is family health promotion, while the dependent variable is the management of patients with Diabetes Mellitus. This study uses "purposive sampling". In this sampling, families that meet the criteria and can represent the characteristics of the population are selected, namely a family with one of the family members suffering from Diabetes Mellitus. Family health promotion significantly provides a change for the better towards improving the role of the family in the management of family members with DM as shown from the pre-test and post-test data which is then tested with the Kendal tau test on all components of the management of family members with DM. There is a significant influence between family health promotion on improving the role of the family in the management of family members with DM at the Kebakramat 1 Health Center where there is an improvement in the role of the family in the management of family members with DM.